Ethnic concentration and language fluency of immigrants in Germany - Alexander M. Danzer; Firat Yaman (Institute for the Study of Labor (IZA), 2010)
Studies that investigate the effect of the regional ethnic composition on immigrant outcomes have been complicated by the self-selection of ethnic minorities into specific neighbourhoods. We analyse the impact of own-ethnic concentration on the language proficiency of immigrants by exploiting the fact that the initial placement of guest-workers after WWII was determined by labour demanding firms and the federal labour administration and hence exogenous to immigrant workers. Combining several data sets, we find a small but robust and significant negative effect of ethnic concentration on immigrants' language ability. Simulation results of a choice model in which location and learning decisions are taken simultaneously confirm the presence of the effect. Immigrants with high learning costs are inclined to move to ethnic enclaves, so that the share of German-speakers would increase only modestly even under the counterfactual scenario of a regionally equal distribution of immigrants across Germany.
Keywords: J61; R23; F22; 330; Enclave; ethnic concentration; language proficiency; immigrants; instrumental variable; random utility model; Migranten; Segregation; Ethnische Gruppe; Sprache; Mehrsprachigkeit; Deutsch; Deutschland